2017
DOI: 10.1039/c7bm00333a
|View full text |Cite
|
Sign up to set email alerts
|

Cell migration on material-driven fibronectin microenvironments

Abstract: Cell migration depends on the physical state of fibronectin, fibrillar vs. globular, which can be controlled by engineering biomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
18
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 48 publications
7
18
1
1
Order By: Relevance
“…If the solution viscosity is too low, it can cause bead formation from the solution dispersing due to the electrostatic field [24]. For further investigation, the surface topography of the substrate was evaluated by using atomic force microscopy (AFM) [25,26]. The fiber stack in a nanofiber scaffold creates porosity.…”
Section: Nanofiber Scaffold Analysismentioning
confidence: 99%
“…If the solution viscosity is too low, it can cause bead formation from the solution dispersing due to the electrostatic field [24]. For further investigation, the surface topography of the substrate was evaluated by using atomic force microscopy (AFM) [25,26]. The fiber stack in a nanofiber scaffold creates porosity.…”
Section: Nanofiber Scaffold Analysismentioning
confidence: 99%
“…17,49,107 Furthermore, previous studies have shown the importance of surface functionalization on cell culture. 108-110 While we have focused on the impact of protein functionalization of graphene – cell interfaces, further investigations are needed to better understand the time-dependent biochemical nature of such interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…These could act as scaffolds to present different growth factors or diffusible chemical signals to cells, on a controllable or stress-related way. Fibronectin, for example, has the ability to bind growth factors such as TGF-β or BMP-2 and keep them in a latent form to be presented to cells (Grigoriou et al 2017 ). Controllable stretching or degradation of these growth factor–bound fibres might not only change the mechanical properties but also causes release of signalling molecules causing them to present to cells in a physiologically relevant way.…”
Section: Ecm Architecture—ii Geometry: Confinement and Topographymentioning
confidence: 99%